2019
DOI: 10.1002/cne.24597
|View full text |Cite
|
Sign up to set email alerts
|

Extensive branching of radially‐migrating neurons in the mammalian cerebral cortex

Abstract: Excitatory neurons of the cerebral cortex migrate radially from their place of birth to their final position in the cortical plate during development. Radially‐migrating neurons display a single leading process that establishes the direction of movement. This leading process has been described as being unbranched, and the occurrence of branches proposed to impair radial migration. Here we have analyzed the detailed morphology of leading process in radially‐migrating pyramidal neurons and its impact on radial m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…The relevance of neuronal migration in the formation of cortical folds is further supported by comparative analyses in mouse and ferret (Gertz and Kriegstein, 2015;Martínez-Martínez et al, 2019). Whereas in mouse cortex radial neuron migration takes place in rather rectilinear trajectories, cortical neurons in ferret display much more tortuous and complex behaviors (Gertz and Kriegstein, 2015).…”
Section: Evolution Of Ecm Components and The Evolution Of Cortical Fomentioning
confidence: 89%
“…The relevance of neuronal migration in the formation of cortical folds is further supported by comparative analyses in mouse and ferret (Gertz and Kriegstein, 2015;Martínez-Martínez et al, 2019). Whereas in mouse cortex radial neuron migration takes place in rather rectilinear trajectories, cortical neurons in ferret display much more tortuous and complex behaviors (Gertz and Kriegstein, 2015).…”
Section: Evolution Of Ecm Components and The Evolution Of Cortical Fomentioning
confidence: 89%
“…The morphology of the leading process varies in different migrating neuronal types, which is considered to reflect an adaptation to the local migratory requirements ( Marin et al, 2010 ; Valiente and Marin, 2010 ). While the majority of radially migrating pyramidal neurons exhibit a simple single leading process ( Martínez-Martínez et al, 2019 ), fast tangentially migrating neurons display a more complex leading process with branched morphologies ( Bellion et al, 2005 ). One cannot exclude the possibility that the differences in the morphodynamics of radial migration is partly correlated to changes in geometry and/or adhesive properties of the extracellular environment in the SP.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study has shown that most of the bipolar neurons exhibit a branched leading process in the ferret, and to a lesser extent in the mouse. These branched processes are less parallel to radial fibers, do not affect radial migration, and importantly, seem to be involved in the remarkable lateral dispersion that occurs in folded cortices (Martínez-Martínez et al, 2019). Indeed, both the dynamic branching and filopodia formation that are observed in the leading process are similar features to those found in neurons exploring their environment during axon guidance (Dent et al, 2011).…”
Section: Tangential Distributionmentioning
confidence: 83%